Data analysis using Microsoft Excel : updated for Office 97 and 98 - Middleton, Michael R. (Pacific Grove, CA : Duxbury, 1999)
Introduction to Excel. Managing files and printing. Basic charts. Univariate numerical data. Categorical data. Bivariate numerical data. Probability distributions...
Keywords: Commercial statistics; Computer programs; Microsoft Excel for Windows; Microsoft Excel for Windows; Commercial statistics -- Computer programs; Business -- Computer programs